Impact of Environmental Pollution in Enggros Tribe Women’s Forest - Syafrina Tijjani; Herdis Herdiansyah; Indra Kertati; Rully Novie Wurarah; Sinan Vidi Lazuardi; Fithrina Nur Rahmadanty Putri; Nafa Febrianti Mutia Dewi; Syahrul Ramadhan; Mochammad Naufal Rizki (Postgraduate, University of Mataram, 2023)
The environment has a close relation to the people, and the condition of the environment affects the livelihood of many people. The condition of women’s forests as the source of livelihood of the Enggros Tribe has been in critical condition. Human activities have been causing a decrease in water quality and increased waste from upstream. This condition has been causing social, economic, and environmental impacts. This study explores women's forests' social, economic, and environmental impact on the Enggros Tribe. The study used in-depth interviews to collect the data. The result of this study shows that the social impact of the women’s forest was that the space of the women of Enggros Tribe had been endangered, and the economic impact has been causing a decrease in the total catch of clams and fish. Also, the environmental impact has been causing the water to become polluted. A serious and effective effort to restore the condition was needed.